Educación superior comparada : el conocimiento, la universidad y el desarrollo - Altbach, Philip G., (Colección de educación superior., 2009)
The book reflects more than three decades of research in the field, and places key elements in the globalization of higher education in a useful framework. Worldwide examples are used to illustrate analyses of such key topics as international exchange, future trends in university development, the complex relationships among academic systems in the industrialized and developing countries, and related issues.